Navigating the digital landscape: evaluating the impacts of digital IMC on building and maintaining destination brand equity - Qi, Meng; Abdullah, Zulhamri; Abdul Rahman, Saiful Nujaimi (Multidisciplinary Digital Publishing Institute, 2024)
In the evolving realm of digital marketing, digital integrated marketing communication (IMC) has emerged as a critical factor in building and maintaining brand equity for sustainable tourism destinations. This research examines the impact of digital IMC consistency and interactivity on establishing destination brand equity, while exploring the interconnections among its various dimensions. Grounded in both empirical and theoretical frameworks, this study collected data via an online questionnaire administered to 435 users of online travel agencies, which was analyzed through Structural Equation Modelling (SEM). The results demonstrate that customer-perceived digital IMC (consistency and interactivity) exerts a significant positive influence on destination brand equity, uncovering the intricate dynamics among destination awareness, image, perceived quality, and loyalty. Notably, destination loyalty is influenced by destination awareness through destination image and perceived destination quality, with destination image having a more significant impact than perceived destination quality. This research is significant in constructing knowledge of IMC in the digital tourism marketing paradigm, shedding light on how the consistency and interactivity of online communication affect various consumer brand equity outcomes. Additionally, it provides valuable insights into digital tourism practices and sustainable development, enriching the discourse regarding how digital IMC enhances destination brand equity.